2019
DOI: 10.1038/s41597-019-0333-x
|View full text |Cite
|
Sign up to set email alerts
|

An extreme sea level indicator for the contiguous United States coastline

Abstract: We develop an aggregated extreme sea level (ESL) indicator for the contiguous United States coastline, which is comprised of separate indicators for mean sea level (MSL) and storm surge climatology (SSC). We use water level data from tide gauges to estimate interannual to multi-decadal variability of MSL and SSC and identify coastline stretches where the observed changes are coherent. Both the MSL and SSC indicators show significant fluctuations. Indicators of the individual components are combined with multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
0
23
2
Order By: Relevance
“…Storm tide distributions (Supplementary Figure 3) are more evenly distributed but still show a skewed upper end tail (Box plots of these distributions are shown in Supplementary Figure 4). Many studies have shown extreme high coastal flood levels from tide gauges follow similar extreme value distributions (Tebaldi et al, 2012;Sweet et al, 2014; US Army Corps of Engineers, 2014; Marcos et al, 2015;Moftakhari et al, 2015;Booth et al, 2016;Rashid et al, 2019). The larger population of tidal peak maximum TWL and skew surge , N = 28,231) from which the Delmarva TC-based storm tides and skew surges were extracted, did indeed closely follow the Normal distribution over the long-term once detrended.…”
Section: Delmarva Tropical Cyclone Storm Tide and Skew Surge Summarymentioning
confidence: 79%
See 1 more Smart Citation
“…Storm tide distributions (Supplementary Figure 3) are more evenly distributed but still show a skewed upper end tail (Box plots of these distributions are shown in Supplementary Figure 4). Many studies have shown extreme high coastal flood levels from tide gauges follow similar extreme value distributions (Tebaldi et al, 2012;Sweet et al, 2014; US Army Corps of Engineers, 2014; Marcos et al, 2015;Moftakhari et al, 2015;Booth et al, 2016;Rashid et al, 2019). The larger population of tidal peak maximum TWL and skew surge , N = 28,231) from which the Delmarva TC-based storm tides and skew surges were extracted, did indeed closely follow the Normal distribution over the long-term once detrended.…”
Section: Delmarva Tropical Cyclone Storm Tide and Skew Surge Summarymentioning
confidence: 79%
“…Wilkerson and Brubaker (2013) investigated the spatial variability of storm surge in the lower Chesapeake Bay over all extreme coastal flooding events but included only a few tropical cyclones. Rashid et al (2019) looked at interannual and multi-decadal variability of extreme storm surge during the peak extratropical (November -April) and tropical (May -October) seasons. Although they included surges from all types of storm events, they concluded that the Mid-Atlantic region varied differently than the Northeast and Southeast portions of the U.S. Atlantic Coast at long time scales.…”
Section: Introductionmentioning
confidence: 99%
“…For example, integrating historical records into the tide gauge record of Venice increases the 50‐year ESL by factor 1.3 (Marcos et al., 2009 ). Decadal variability of 50‐year ESL has been found to lie at around 10 cm (Marcos et al., 2015 ; Menendez & Woodworth, 2010 ; Rashid et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…We use hourly sea level data from the National Oceanic and Atmospheric Administration (NOAA; http://tidesandcurrents.noaa.gov/) database. Following Rashid et al (2019), we identify 35 sites (Fig. 1) with long records extending back to 1950 or earlier and where time series at individual sites are 80% or more complete.…”
Section: Storm Surgementioning
confidence: 99%